(untitled) (Marketing Journal, 2025)
On the one hand, the cluster allows you to quickly update according to the trigger effect. On the other hand, in doing so, it forces buyers to remember their constant development in front of the market. On the other hand, the stability of a cluster is determined by the ability to withstand external and internal negative disturbances and maintain a balanced and stable state. Over a long period of time, movement has relatively the same structure, mode of action and trajectory. It is the cluster economy that allows you to build a new business concept, change the usual models, position yourself differently and find new areas of competitiveness. 105 Kеywords: Clustеr, industry clustеrs, locаl industry, еntrеprеnеurship, synеrgistic еffеct, triggеr еffеct, “Frее mаrkеt” of clustеrs аnd polаr thеory.